The links between implementing ISA 540 and mitigating the practice of smoothing reported net earnings using write-offs of accounts receivable and inventory by reporting entities in Poland - Andrzej Piosik (Zeszyty Teoretyczne Rachunkowości, 2016)
The paper addresses the question of the links between implementing ISA 540 and mitigating the practice of smoothing reported net earnings using write-offs of accounts receivable and inventory by reporting en-tities in Poland. The research question stems from the previous analysis carried out by the author in which evidence was provided that reporting entities in Poland in the period 2000–2010 effectively used write-offs of accounts receivable and inventory in order to mitigate fluctuations of reported net earnings. This paper provides evidence that before implementing ISA 540 reporting entities used write-offs of receivables and inventory for income smoothing in effective manner, however in the period after implementing the standard (2009–2014) no link was observed between the write-offs and reduced fluctuations of reported net earnings. The research has been carried out using Wilcoxon signed-rank test used to check equality of medians of mean deviations of net earnings before write-offs of receivables and inventory and mean deviations of net earnings after write-offs. For the period before implementing ISA 540 there are grounds to reject the hy-pothesis of equality of medians of mean deviations of net earnings, however in the post-adoption period there is no justification to reject the hypothesis of equality of medians. The research provides evidence of positive impact of ISA 540 mitigating the processes of accounting earnings management. The indicated regularity does not apply to banks, because within this group of companies we have not observed the use of write-offs of loan receivables in order to reduce the variability of net earnings before implementing ISA 540 and in the period following the implementation of the standard.